The Extension of Noncommutative Modified KP Hierarchy and Its Quasideterminant Solutions - Hongxia Wu; Chunxia Li; Haifeng Wang (Axioms)
The extended noncommutative modified KP (exncmKP) hierarchy is firstly constructed, which gives rise to two types of the ncmKP equation with self-consistent sources (ncmKPESCSs). Then, the noncommutative (NC) Miura transformation between the extended noncommutative KP (exncKP) hierarchy and the exncmKP hierarchy is presented, and the quasideterminant solutions of the exncmKP hierarchy are also given. As its byproduct, the quasideterminant solutions of two types of ncmKPESCSs are obtained. The matrix solutions of two types of ncmKPESCSs are finally investigated, and the impact of the source terms on the NC soliton is analyzed.